2008
DOI: 10.4049/jimmunol.181.10.7307
|View full text |Cite
|
Sign up to set email alerts
|

A New Mechanism for Inhalational Priming: IL-4 Bypasses Innate Immune Signals

Abstract: Signaling via innate immune mechanisms is considered pivotal for T cell-mediated responses to inhaled Ags. Furthermore, Th2 cells specific for one inhaled Ag can facilitate priming of naive T cells to unrelated new inhaled Ags, a process we call “Th2 collateral priming”. Interestingly, our previous studies showed that collateral priming is independent of signals via the innate immune system but depends on IL-4 secretion by CD4+ T cells. We thus hypothesized that IL-4 can bypass the need for signals via the inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 57 publications
(78 reference statements)
2
35
0
3
Order By: Relevance
“…Furthermore, when mice were given an intranasal application of ovalbumin (ova) during this peak inflammatory response, they developed sensitization to ova, in the form of airway hyperresponsiveness upon later antigen challenge, without the requirement of previous extrapulmonary sensitization. This sensitization proved to be dependent on interleukin-4 (IL-4) signaling, which has previously been described to be a hallmark of collateral sensitization (10). We also found that the degree of exposure to the exogenous antigen (ova) required to cause sensitization was less during a Pneumocystis infection than what has been reported for other early respiratory infections, such as those caused by RSV (45).…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…Furthermore, when mice were given an intranasal application of ovalbumin (ova) during this peak inflammatory response, they developed sensitization to ova, in the form of airway hyperresponsiveness upon later antigen challenge, without the requirement of previous extrapulmonary sensitization. This sensitization proved to be dependent on interleukin-4 (IL-4) signaling, which has previously been described to be a hallmark of collateral sensitization (10). We also found that the degree of exposure to the exogenous antigen (ova) required to cause sensitization was less during a Pneumocystis infection than what has been reported for other early respiratory infections, such as those caused by RSV (45).…”
mentioning
confidence: 38%
“…More recent studies have characterized a more general model in which inhalational sensitization occurs in the lung during an ongoing inflammation (10). Because this sensitization can occur to antigens unrelated to the original infection or inflammation, the authors have termed this "collateral sensitization."…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrated that bystander cells exposed to ambient IL-4 signalling in a Th2 active lymph node became functionally biased, such that their response to a subsequent, antigen-specific stimulus resulted in unexpected Th2 polarisation [66]. A similar phenomenon has been observed during allergic asthma and was described as 'collateral priming' [70,71].…”
Section: Il-4 Signalling To Bystander Cellsmentioning
confidence: 54%
“…Likewise, the time point used around 72 h also had been reported in other animal models, including mammals. For example, in vivo treatment with recombinant IL-4 for 72 h directly increased dendritic cell (DC) maturation and T cell recruitment independent of innate immune signals in a mouse model (63). According to these observations, it could be considered that the function of IL-4 is a critical driver in the priming and initiation of Th2-type adaptive immunity and is crucial for the recruitment, maturation, and activation of DCs and T lymphocytes by upregulating a number of key regulatory factors, such as CD40, CD154, CD80/86, CD83, and DC-SIGN/CD209.…”
Section: Discussionmentioning
confidence: 99%